Mn-based metal organic framework derived Mn2O3 / Mn3O4 heterojunction material as well as preparation method and application thereof
The preparation of Mn2O3/Mn3O4 heterojunction material by calcining in the reaction of manganese salt, surfactant and benzoic acid compounds has been solved, and the problems of complexity and high cost of synthesis of Mn-based oxide catalysts in the prior art have been significantly improved. The electrochemical properties and cycle stability of sulfur batteries provide high-efficiency electrode materials for other energy storage devices.
Patent Information
- Application Number
- CN202411220326.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to effectively synthesize low-cost and high-efficiency Mn-based oxide catalysts, which limits the application potential of lithium-sulfur batteries, and traditional synthesis methods are complex and difficult to control.
The Mn2O3/Mn3O4 heterojunction material was prepared as a catalyst for lithium sulfur batteries by reacting in a solvent, and calcining in an inert atmosphere and air.
It has achieved the improvement of the electrochemical performance of lithium-sulfur batteries, extended the cycle life, and provided high-efficiency electrode materials for other energy storage devices. It has a simple process, low cost and is suitable for industrial production.
Smart Images

Figure CN119306256A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nano material preparation method and electrocatalytic cross application, and specifically relates to a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, and a preparation method and application thereof. Background Art
[0002] Energy and environment are important foundations and key guarantees for human survival and social development. The massive consumption of traditional energy resources (coal, oil, and natural gas, etc.) has not only exacerbated the energy crisis, but also caused a series of problems such as climate warming and environmental pollution. Faced with the two major challenges of energy shortage and environmental pollution, the development of new clean and sustainable energy systems has become the key to the long-term stable development of human society. Therefore, the development of low-cost, high-energy and environmentally friendly energy storage devices is extremely important. As we all know, the advent of lithium-ion batteries has brought a lot of convenience to our daily lives, such as the use of micro-electronic products such as mobile phones and laptops. However, with the development of science and technology and the improvement of quality of life, lithium-ion batteries cannot meet people's current needs due to their limited energy density, so the development of energy storage devices with higher energy density has become more and more urgent. Lithium-sulfur batteries are considered to be the most promising next-generation energy storage system because of their high theoretical energy density (2600Wh / kg), abundant sulfur reserves, low price and environmental friendliness. However, lithium-sulfur batteries have serious restrictions on their commercial application potential due to the insulation of sulfur, slow reaction kinetics and severe shuttle effect. Therefore, the development of catalytic materials that can promote the conversion of lithium polysulfide is of great research significance for improving the electrochemical performance of lithium-sulfur batteries.
[0003] Metal oxides have strong adsorption and catalytic conversion effects on lithium polysulfide, which can inhibit the dissolution of lithium polysulfide, thereby extending the cycle life of lithium-sulfur batteries. Therefore, they are considered to be a lithium-sulfur battery catalyst with great application potential. Lindar Nazar's group proposed in the "Goldilocks" principle that metal oxides have a strong adsorption and catalytic conversion effect on lithium polysulfide, which can inhibit the dissolution of lithium polysulfide, thereby extending the cycle life of lithium-sulfur batteries. +The potential of the oxide is divided into three categories. When the oxide potential is moderate, thiosulfate is generated during the electrochemical reaction at the sulfur positive electrode, which is most suitable for use as a positive electrode carrier for lithium-sulfur batteries. Among them, Mn-based metal oxides (δ-MnO2) belong to this type of material. On the other hand, Mn-based metal oxides can effectively inhibit the shuttle effect of lithium polysulfide due to their good structural stability and strong chemical anchoring effect on soluble lithium polysulfide, and are a very promising sulfur host material. Metal heterojunction catalysts are also considered to be one of the effective methods for synthesizing efficient catalyst materials because they can integrate or even surpass the advantages of two separate catalysts. In previous reports, Mn-based metal oxides are mostly synthesized by co-precipitation or template methods. These methods are usually complicated and difficult to control, which increases the cost of the final product. More importantly, they limit the potential application of Mn-based oxide materials in various fields such as energy catalysis and environmental governance.
[0004] Therefore, the development of a simple, controllable, low-cost, high-yield, green and low-pollution synthesis method is not only of great research value for Mn-based oxide materials in the field of energy catalysis, but also of great significance for expanding its application in other industries. Summary of the invention
[0005] The present invention is made to solve the above-mentioned problems, and aims to provide a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework and a preparation method and application thereof.
[0006] The present invention provides a method for preparing a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, which has the following characteristics and comprises the following steps: S10, reacting a manganese salt, a surfactant and a benzoic acid compound in a solvent to obtain a Mn-based metal organic framework material; S20, calcining the Mn-based metal organic framework material in an inert atmosphere to obtain a carbonized product; S30, flattening the carbonized product, and calcining it in an air atmosphere to obtain a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework.
[0007] In the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention, it can also have the following characteristics: wherein the manganese salt includes manganese acetate tetrahydrate and / or manganese nitrate tetrahydrate, the surfactant includes polyvinyl pyrrolidone with a molecular weight of 30,000 to 1,300,000, the benzoic acid compound includes any one or more of terephthalic acid, trimesic acid or 2,5-dihydroxyterephthalic acid, the solvent includes ethanol aqueous solution or DMF, and the volume fraction of ethanol in the ethanol aqueous solution is 1 / 3 to 2 / 3.
[0008] In the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention, it can also have the following characteristics: wherein the molar ratio of the manganese salt, the surfactant and the benzoic acid compound is (3.5-4.5):(0.0046-0.2):(8-9).
[0009] In the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention, it can also have the following characteristics: wherein, step S10 includes the following sub-steps: S11, adding a manganese salt and a surfactant into a solvent and mixing them to obtain a first solution, and adding a benzoic acid compound into the solvent to obtain a second solution; S12, slowly adding the second solution dropwise to the first solution and stirring to obtain a reaction solution containing the Mn-based metal organic framework material; S13, centrifugally separating the Mn-based metal organic framework material from the reaction solution, and then washing and drying.
[0010] In the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention, it can also have the following characteristics: wherein, in step S12, the dripping method is a microneedle injection method, and the injection flow rate is 0.1mL / min to 20mL / min. In step S12, after the stirring is completed, the reaction liquid is also aged at room temperature or placed in a forced air drying oven for solvent thermal reaction.
[0011] The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention may also have the following characteristics: wherein, in step S12, the stirring method is stirring at room temperature for 0.1h to 1h, and the aging time is 6h to 24h.
[0012] In the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention, it can also have the following characteristics: wherein, in step S20, the inert atmosphere is N2, Ar or a mixture of H2 and Ar with a volume ratio of 0.5:9.5, and the calcination method is: heating to 400℃-800℃ in a tubular furnace at a heating rate of 2℃ / min~10℃ / min and calcining for 1h~3h and then cooling to room temperature.
[0013] In the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework provided by the present invention, it can also have the following characteristics: wherein, in step S30, the calcination method is: heating to 500℃~1000℃ in a tubular furnace at a heating rate of 2℃ / min~10℃ / min and calcining for 1h~5h and then cooling to room temperature.
[0014] The present invention also provides a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, which has the following characteristics: it is prepared by any of the aforementioned methods for preparing a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework.
[0015] The present invention also provides an application of a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework in a sulfur positive electrode reaction of a lithium-sulfur battery, which has the following characteristics: the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework is used as an electrocatalyst.
[0016] Functions and Effects of the Invention
[0017] The present invention utilizes a green and simple method to controllably synthesize Mn-based metal oxide / metal oxide heterojunction materials with different valence states.
[0018] The present invention adopts simple inorganic salts as reactants, has abundant reserves of raw materials, low industrial cost, and can controllably synthesize Mn-BTC metal organic framework precursors, and then obtains Mn2O3, Mn2O3 / Mn3O4 or Mn3O4 respectively by regulating the calcination temperature. The method is novel and has certain universality, and can provide ideas for the efficient and controllable synthesis of other metal oxides.
[0019] The product prepared by the present invention has good electrochemical performance of lithium-sulfur batteries, can be used as an efficient sulfur redox catalytic material, and can also be used as an electrode material for other energy storage devices such as aqueous zinc batteries, and has a relatively broad development prospect and application space.
[0020] The invention has simple process, mild preparation conditions, stable product morphology, high purity, high yield, convenient and simple product processing, and is suitable for medium-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flowchart of a method for preparing a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to an embodiment of the present invention;
[0022] Figure 2 is the X-ray powder diffraction (XRD) pattern of sample 1 of an embodiment of the present invention;
[0023] Figure 3 This is a SEM image of the intermediate product Mn-BTC in the preparation process of Sample 1 of the embodiment of the present invention at a magnification of 1 μm;
[0024] Figure 4 is a SEM image of sample 1 of an embodiment of the present invention;
[0025] Figure 5is the X-ray powder diffraction (XRD) pattern of sample 2 of an embodiment of the present invention;
[0026] Figure 6 is a SEM image of sample 2 of an embodiment of the present invention;
[0027] Figure 7 is the X-ray powder diffraction (XRD) pattern of sample 3 of an embodiment of the present invention;
[0028] Figure 8 is a SEM image of sample 3 of an embodiment of the present invention;
[0029] Fig. 9 This is a SEM image of the intermediate product Mn-BTC in the preparation process of sample 4 of the embodiment of the present invention at a magnification of 500nm;
[0030] Fig.10 is a SEM image of sample 4 of an embodiment of the present invention;
[0031] Fig.11 is a SEM image of the intermediate product Mn-BTC in the preparation process of sample 5 of the embodiment of the present invention at a magnification of 5 μm;
[0032] Fig.12 is a SEM image of sample 5 of an embodiment of the present invention;
[0033] Fig.13 1 is the EIS curve of the cathode when samples 1, 2 and 3 in the test example of the present invention are used as sulfur positive electrode catalysts of lithium-sulfur batteries;
[0034] Fig.14 The graphs of battery cycle stability at a current density of 0.2C when samples 1, 2 and 3 in the test examples of the present invention are used as sulfur cathode catalysts for lithium-sulfur batteries respectively;
[0035] Fig.15 It is a battery cycle stability diagram at a current density of 0.2C when samples 4, 5 and 6 in the test example of the present invention are used as sulfur positive electrode catalysts of lithium-sulfur batteries. DETAILED DESCRIPTION
[0036] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments, in conjunction with the accompanying drawings, specifically describe a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework and its preparation method and application.
[0037] <Example>
[0038] Figure 1It is a flowchart of a method for preparing a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to an embodiment of the present invention.
[0039] like Figure 1 As shown, this embodiment provides a method for preparing a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, comprising the following steps:
[0040] S10, preparing a Mn-based metal organic framework material, specifically comprising the following sub-steps S11 to S13:
[0041] S11, put 98 mg of manganese salt and 600 mg of polyvinyl pyrrolidone into 20 mL of 50% by volume ethanol aqueous solution and stir at room temperature for 30 min until completely dissolved to obtain a first solution; put 180 mg of trimesic acid into 20 mL of 50% by volume ethanol aqueous solution and stir at room temperature for 30 min until completely dissolved to obtain a second solution.
[0042] S12, under slow stirring conditions, the second solution is slowly added to the first solution at a dripping rate of 1 mL / min using a microneedle injection method, followed by stirring at room temperature for 10 min, aging at room temperature for 24 h, or solvent thermal reaction at 160° C. in a forced air drying oven for 12 h to obtain a reaction solution containing a Mn-based metal organic framework material.
[0043] S13, separating the Mn-based metal organic framework material from the reaction solution by centrifugation, washing with ethanol for 5 times, and vacuum drying at 60° C. for 12 h. The obtained white product is the desired Mn-based metal organic framework material (Mn-BTC).
[0044] S20, pouring the Mn-BTC obtained in step S13 into a porcelain boat, and then transferring it to a tubular furnace, heating it to 570°C at a heating rate of 10°C / min in an Ar gas atmosphere, calcining it for 2 hours, and then cooling it to room temperature to obtain a carbonized product (MnO / C).
[0045] S30, MnO / C is placed in a porcelain boat and flattened, then transferred to a tube furnace, and calcined to T°C in air at a heating rate of 5°C / min for 3 hours, and after the tube furnace is cooled to room temperature, a Mn-based metal organic framework-derived Mn2O3 / Mn3O4 heterojunction material is obtained.
[0046] This embodiment also provides a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, which is prepared by the preparation method of the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework in this embodiment.
[0047] Among them, a total of 6 Mn-based metal-organic framework-derived Mn2O3 / Mn3O4 heterojunction materials were prepared, and their materials were any one of Mn2O3, Mn3O4 or Mn2O3 / Mn3O4, which were respectively recorded as sample 1, sample 2, sample 3, sample 4, sample 5 and sample 6. The specific parameters of samples 1 to 6 in the preparation process are shown in Table 1.
[0048] Table 1 (Specific parameters of samples 1 to 6 during the preparation process)
[0049]
[0050]
[0051] Figure 2 is the X-ray powder diffraction (XRD) pattern of sample 1 of the embodiment of the present invention.
[0052] like Figure 2 As shown, the XRD spectrum of sample 1 shows clear diffraction peaks of Mn2O3 (PDF#71-0636) and Mn3O4 (PDF#89-4837), indicating the successful synthesis of Mn2O3 / Mn3O4 heterojunction materials.
[0053] Figure 3 It is a SEM image of the intermediate product Mn-BTC in the preparation process of Sample 1 of the embodiment of the present invention at a magnification of 1 μm.
[0054] like Figure 3 As shown, the Mn-BTC corresponding to sample 1 has a regular spherical structure, which is a hollow sphere self-assembled from numerous small cubic columns with a relatively uniform size of about 2 μm.
[0055] Figure 4 This is a SEM image of sample 1 of the embodiment of the present invention, wherein image a is a magnification of 20 μm, image b is a magnification of 5 μm, and image c is a magnification of 2 μm.
[0056] like Figures 2 to 4 As shown, after the Mn-BTC corresponding to sample 1 undergoes the calcination process, the morphology of the derived Mn2O3 / Mn3O4 heterojunction material (sample 1) changes significantly, the hollow porous spherical structure becomes more obvious, the surface becomes smoother, and the pores on the surface become larger.
[0057] Figure 5 is the X-ray powder diffraction (XRD) pattern of sample 2 of the embodiment of the present invention.
[0058] like Figure 5As shown, the XRD spectrum of sample 2 shows clear X-ray diffraction peaks, which correspond one to one with the standard PDF card (PDF#71-0636) of Mn2O3, indicating the successful synthesis of Mn2O3 material.
[0059] Figure 6 This is a SEM image of sample 2 of the embodiment of the present invention, wherein image a is magnified by 10 μm, and images b and c are magnified by 1 μm.
[0060] like Figure 6 As shown, the calcined sample 2 (Mn2O3 material) has a hollow porous spherical shape with an uneven surface, but the pore size is smaller than that of the Mn2O3 / Mn3O4 heterojunction material, and the surface becomes smoother. The particle size ranges from about 2μm to 5μm.
[0061] Figure 7 is the X-ray powder diffraction (XRD) pattern of sample 3 of the embodiment of the present invention.
[0062] like Figure 7 As shown, the XRD spectrum of sample 3 shows clear X-ray diffraction peaks, which correspond one to one with the standard PDF card of Mn3O4 (PDF#89-4837), indicating the successful synthesis of Mn3O4 material.
[0063] Figure 8 This is a SEM image of sample 3 of the embodiment of the present invention, wherein image a is a magnification of 20 μm, and images b and c are magnifications of 5 μm.
[0064] like Figure 8 As shown, the morphology of sample 3 (Mn3O4 material) obtained by calcination is a hollow porous sphere with an uneven surface, but the size of the pores is larger than that of the Mn2O3 / Mn3O4 heterojunction material, the surface becomes rougher, and the particle size is about 5μm.
[0065] Fig. 9 This is a SEM image of the intermediate product Mn-BTC in the preparation process of Sample 4 of an embodiment of the present invention at a magnification of 500nm.
[0066] like Fig. 9 As shown in the figure, the morphology of Mn-BTC corresponding to sample 4 is still a spherical structure, which is a hollow sphere self-assembled from numerous small particles. The size is relatively uniform, about 400nm, and the spherical surface is also rough. However, compared with the Mn-BTC corresponding to sample 1, the size is significantly reduced, and the gaps between the small particles of the assembled spherical Mn-BTC are larger.
[0067] Fig.10This is a SEM image of sample 4 of the embodiment of the present invention, wherein the magnification is 300 nm.
[0068] like Fig.10 As shown, in sample 4 (Mn2O3 / Mn3O4 heterojunction material) obtained after calcination, most of the spherical Mn-BTC collapsed from the surface inward into a bowl-shaped structure, the surface became smooth, and was accompanied by more cracks.
[0069] Fig.11 It is a SEM picture of the intermediate product Mn-BTC in the preparation process of sample 5 of the embodiment of the present invention at a magnification of 5 μm.
[0070] like Fig.11 As shown, the Mn-BTC morphology corresponding to sample 5 is still a spherical structure, which is a hollow sphere self-assembled from numerous small cubic columns with a relatively uniform size of about 3 μm.
[0071] Fig.12 This is a SEM image of sample 5 of the embodiment of the present invention, wherein the magnification is 5 μm.
[0072] like Fig.12 As shown, in the sample 5 (Mn2O3 / Mn3O4 heterojunction material) obtained after calcination, the morphology has no obvious change and is still a spherical structure. The excess surfactant on the surface becomes smooth after oxidation, and the pores become larger and more numerous.
[0073] <Test example>
[0074] This test example tests the electrochemical performance of several samples prepared in the examples, thereby providing an application of a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework in a sulfur positive electrode reaction of a lithium-sulfur battery. The Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework is used as a positive electrode catalyst.
[0075] The test method in this test example is as follows: the composite material of the sample prepared in the example and S is used as the cathode, the metal lithium sheet is used as the negative electrode, Celgard 2500 is used as the diaphragm, and the electrolyte is 1.0M lithium bis(trifluoromethanesulfonyl)imide and 0.15M lithium nitrate dissolved in a mixed solution of 1,3-dioxolane and ethylene glycol dimethyl ether, and assembled into a button cell in a glove box. The assembled button cell was subjected to electrochemical impedance spectroscopy (EIS) test using a CHI 760E electrochemical workstation. The test frequency range of EIS was 0.01Hz to 105Hz, and the amplitude was 5mV. Wuhan Blue Electric was used to test the cycle performance of the assembled button cell, and a cycle test of 300 cycles was performed at a current density of 0.2C (1C = 1675mAh / g) to investigate the electrochemical stability of the catalyst.
[0076] The preparation process of the cathode (working electrode) is as follows: the sample prepared in the example and S are heated by a low-temperature melting method at 155°C for 12 hours to obtain a S / Mn2O3 / Mn3O4 composite material, and then the S / Mn2O3 / Mn3O4 composite material, carbon black (as a conductive agent) and polyvinylidene fluoride (as a binder) are mixed in a mass ratio of 7:2:1, and a dispersant NMP is added, and stirred for 12 hours in a sealed and dry environment, and then the stirred slurry is coated on aluminum foil and dried in a vacuum oven at 60°C for 12 hours. After drying, it is cut into small discs with a 13mm cutter for standby use.
[0077] Fig.13 These are the EIS curves of the cathode when samples 1, 2 and 3 in the test examples of the present invention are used as sulfur positive electrode catalysts of lithium-sulfur batteries.
[0078] like Fig.13 As shown, the battery assembled with S / Mn2O3 / Mn3O4 (sample 1) cathode has the smallest charge transfer resistance and diffusion resistance, followed by S / Mn3O4 (sample 3), and the impedance of S / Mn2O3 (sample 2) is the largest, indicating that the S / Mn2O3 / Mn3O4 (sample 1) cathode has higher conductivity and better electrochemical kinetics
[0079] Fig.14 It is a battery cycle stability diagram at a current density of 0.2C when samples 1, 2 and 3 in the test example of the present invention are used as sulfur positive electrode catalysts of lithium-sulfur batteries.
[0080] like Fig.14 As shown, the battery assembled with S / Mn2O3 / Mn3O4 (sample 1) cathode cycles 300 times at a current density of 0.2C, with a capacity decay rate of 0.49% per cycle, while the capacity decay rates of S / Mn3O4 (sample 3) and S / Mn2O3 (sample 2) per cycle are 1.12% and 1.68%, respectively. This proves that the S / Mn2O3 / Mn3O4 (sample 1) cathode can effectively inhibit the shuttle of lithium polysulfide and efficiently catalyze the conversion of lithium sulfide.
[0081] Fig.15 It is a battery cycle stability diagram at a current density of 0.2C when samples 4, 5 and 6 in the test example of the present invention are used as sulfur positive electrode catalysts of lithium-sulfur batteries.
[0082] like Fig.15 As shown, sample 4 cycles 300 times at a current density of 0.2C, with a capacity decay rate of 0.86% per cycle; sample 5 cycles 300 times at a current density of 0.2C, with a capacity decay rate of 0.56% per cycle; sample 6 cycles 300 times at a current density of 0.2C, with a capacity decay rate of 1.3% per cycle.
[0083] like Figures 13-15 As shown, Mn2O3 / Mn3O4 heterojunction materials can significantly improve the electrochemical performance of lithium-sulfur batteries and have very important research value in the field of energy catalysis.
[0084] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, characterized in that: The following steps are involved: S10, reacting a manganese salt, a surfactant and a benzoic acid compound in a solvent to obtain a Mn-based metal organic framework material; S20, calcining the Mn-based metal organic framework material in an inert atmosphere to obtain a carbonized product; S30, after flattening the carbonized product, calcining it in an air atmosphere to obtain the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework.
2. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to claim 1, characterized in that: in, The manganese salt includes manganese acetate tetrahydrate and / or manganese nitrate tetrahydrate, The surfactant includes polyvinyl pyrrolidone with a molecular weight of 30,000 to 1,300,000. The benzoic acid compound includes any one or more of terephthalic acid, trimesic acid or 2,5-dihydroxyterephthalic acid. The solvent includes ethanol aqueous solution or DMF, and the volume fraction of ethanol in the ethanol aqueous solution is 1 / 3 to 2 / 3.
3. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to claim 1, characterized in that: in, The molar ratio of the manganese salt, the surfactant and the benzoic acid compound is (3.5-4.5):(0.0046-0.2):(8-9).
4. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to any one of claims 1 to 3, Features: Wherein, step S10 includes the following sub-steps: S11, adding the manganese salt and the surfactant into the solvent to obtain a first solution, and adding the benzoic acid compound into the solvent to obtain a second solution; S12, slowly dropping the second solution into the first solution and stirring to obtain a reaction solution containing the Mn-based metal organic framework material; S13, separating the Mn-based metal organic framework material from the reaction solution by centrifugation, and then washing and drying.
5. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to any one of claim 4, characterized in that: in, In step S12, the dripping method is microneedle injection, and the injection flow rate is 0.1 mL / min to 20 mL / min. In step S12, after the stirring is completed, the reaction solution is aged at room temperature or placed in a forced air drying oven for solvent thermal reaction.
6. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to claim 5, characterized in that: in, In step S12, the stirring method is stirring at room temperature for 0.1 h to 1 h, and the aging time is 6 h to 24 h.
7. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to claim 1, characterized in that: in, In step S20, the inert atmosphere is N2, Ar, or a mixture of H2 and Ar in a volume ratio of 0.5:9.
5. The calcination method is as follows: heating to 400°C-800°C in a tubular furnace at a heating rate of 2°C / min-10°C / min, calcining for 1h-3h, and then cooling to room temperature.
8. The method for preparing the Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework according to claim 1, characterized in that: in, In step S30, the calcination method is: heating to 500°C to 1000°C in a tube furnace at a heating rate of 2°C / min to 10°C / min, calcining for 1h to 5h, and then cooling to room temperature.
9. A Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework, characterized in that: The material is prepared by the method for preparing Mn2O3 / Mn3O4 heterojunction material derived from a Mn-based metal organic framework as described in any one of claims 1 to 8.
10. Application of the Mn2O3 / Mn3O4 heterojunction material derived from the Mn-based metal organic framework as claimed in claim 9 in the sulfur positive electrode reaction of a lithium-sulfur battery, in, The Mn-based metal organic framework derived Mn2O3 / Mn3O4 heterojunction material is used as an electrocatalyst.
Citation Information
Cited By
Preparation method of manganese metal organic framework material and application of manganese metal organic framework material in aqueous zinc battery
CN119875136A
Photocatalyst for photocatalytic synthesis of ammonia and preparation method thereof
CN122164506A